Synthesis, Characterization and Biological Effect Study of Some New Azo and Azo–Chalcone Compounds Derived from 2, 6-Diaminopyridine - Nihad I. Taha (Journal of Global Pharma Technology, 2016)
The objective of this work was to prepare azo and azo-chalcones derivatives out of 2, 6- diaminopyridine (2, 6-DAP) which has extensive use in the synthesis of pharmaceutical compounds. The azo-diamine (S1-S6) was prepared from the coupling reaction of diazonium salt prepared from various substituted aromatic amines with 2, 6-diaminopyridine. The product (S1) was reacted in basic condition with one equivalent of different substituted aromatic aldehydes in methanol to give ten new azo-chalcones (S2-S11) in good yields. The final products were identified by their physical properties besides their UV-visible, FTIR and 1H NMR spectra. Biological activity of the compounds (S1-S6) was investigated and compounds (S1 and S2) showed high activity against B. subtilis and E. coli.Keywords: Azo- Chalcone, 2, 6-Diaminopyridine, diazonium salt, Pyridine.